Improving Work Ability of Mentally Burdened Emerging Adults in Vocational Integration Programs: A Study Protocol - Sabatella, Filomena; von Wyl, Agnes (Frontiers in Psychology, 2019)
Background: Emerging adults who do not successfully transition from compulsory education to the upper secondary level have a greater risk of developing mental illness than their working peers. Early intervention is important in these cases; the course of an illness can be positively influenced if treated early and without delay, and consequently, the illness will not affect the professional and personal development of the emerging adults any further. Postponing treatment of a mental illness increases the risk of chronification of the disease. Up to now, vocational integration programs have been mostly educationally oriented. To recognize and treat mental illness in a timely way, we developed an intervention that includes psychotherapy support in a vocational integration program for emerging adults who have not successfully transitioned from compulsory education to the upper secondary level. Aim: The aim of this study is to investigate the effectiveness of the described intervention, which will be delivered to all emerging adults aged 16–29 entering the vocational integration program. Another objective is to determine if it is worthwhile and feasible to proceed with testing the intervention in a full-scale clinical trial. Conducting research with this population can be very difficult, which makes it especially important to test the feasibility of a clinical trial. Methods: A single group clinical trial will be conducted to examine the effectiveness of the intervention described above. Emerging adults aged 16–29 entering a vocational integration program will be recruited. Participants will provide informed consent and complete pre-intervention measures; they then take part in the intervention group in addition to the regular vocational integration program. The primary outcomes for this study are an increase in work ability, mental health literacy, and mental health. Demographic information, vocational biography, and satisfaction with the intervention will also be collected. Questionnaire data will be collected at pre-intervention, post-intervention, and 6-month follow-up. Ethics and dissemination: The study was approved by the Ethics Committee of the Canton of Zurich (2017-00936) and registered in https://clinicaltrials.gov (NCT03328286) before recruitment started. The results will be reported in future scientific publications and international conference presentations.